Enhanced supercapacitor performance of a 3D architecture tailored using atomically thin rGO–MoS2 2D sheets. Issue 96 (29th September 2016) - Jose, Sujin P.; Tiwary, Chandra Sekhar; Kosolwattana, Suppanat; Raghavan, Prasanth; Machado, Leonardo D.; Gautam, Chandkiram; Prasankumar, T.; Joyner, Jarin; Ozden, Sehmus; Galvao, Douglas S.; Ajayan, P. M.
Abstract : A stable, conductive, additive-free and scalable 3D architecture supercapacitor electrode fabricated by atomically thin 2D sheets of GO and MoS2 shows superior electrochemical properties which are further substantiated using MD simulations. Abstract : A 3D architecture is fabricated using 2D nano-sheets of GO and MoS2 as the building blocks by a facile, one-pot chronoamperometry method to achieve a conductive additive free, binder free and scalable supercapacitor electrode. The superior electrochemical properties of the 3D PPy-rGO–MoS2 (PGMo) are due to its porous structure, thin wall, high surface area and high electrical conductivity that endow rapid transportation of electrolyte ions and electrons throughout the electrode matrix. The synergistic effect between the components in a proper ratio improves the supercapacitor performance and material stability of PGMo. The possible correlation of the structure and electrochemical performance of the 3D ternary composite is backed by a fully atomistic molecular dynamics (MD) simulation study. The high specific capacitance (387 F g −1 ) and impressive cycling stability (>1000 cycles) estimated for PGMo open up an opportunity to consider the 3D ternary nanostructures as cutting edge materials for energy storage solutions.